2009
DOI: 10.7547/0980223
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of the Podiatrist and the DPM Degree

Abstract: Although there are gaps in the public knowledge, our study revealed a greater familiarity with podiatry and the DPM degree than originally thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Further supporting this hypothesis are the results of the Malaysian study, which showed that participants with a higher educational level and employed in the health and educational sectors had a greater level knowledge of communication disorders and the role of speech pathologists 11 . Two studies within other allied health disciplines have also reported a relationship between participants’ area of employment and their awareness of the profession 12,25 …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Further supporting this hypothesis are the results of the Malaysian study, which showed that participants with a higher educational level and employed in the health and educational sectors had a greater level knowledge of communication disorders and the role of speech pathologists 11 . Two studies within other allied health disciplines have also reported a relationship between participants’ area of employment and their awareness of the profession 12,25 …”
Section: Discussionmentioning
confidence: 83%
“…For example, an Australian study on public perception of physiotherapy reported that while the public knew that physiotherapists work with musculoskeletal conditions, they had very little awareness that physiotherapists work with children or other services available within the discipline's scope of practice 16 . Though limited, studies on public awareness across speech pathology, physiotherapy, occupational therapy, audiology, podiatry and chiropractic all highlight the need for educational campaigns to promote the full range of services offered by these allied health professions 7‐25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation